The Influence of Incentives, Rewards, and Work Facilities on Employee Job Satisfaction at Perumda Air Minum Surya Sembada Surabaya - Nabilah, Raden Roro Aurora Evvatun; Samsudin, Acep (Value Added : Majalah Ekonomi dan Bisnis, 2026)
This study aims to investigate and analyze the impact of incentives, rewards, and work facilities on employee job satisfaction at Perumda Air Minum Surya Sembada, Surabaya. Utilizing an associative quantitative approach, this research employed a saturated sampling technique to include a total of 35 employees as respondents. Data analysis was conducted through multiple linear regression using SPSS 31 software to ensure precise statistical results. The findings demonstrate that, simultaneously, the variables of incentives (X1), rewards (X2), and work facilities (X3) have a significant effect on employee job satisfaction (Y). While the partial effects may vary, the overall model suggests that work facilities serve as a critical factor in enhancing the workplace experience. These results provide empirical evidence for the management of Perumda Air Minum Surya Sembada to strategically optimize their rewards systems and infrastructure to maintain high levels of employee contentment.